# Algebra 2

posted by .

Simplify (3^−2 − 2^−2)^−1

The answer is -36/5 I just need to know how to do it.

• Algebra 2 -

3^-2 = 1/3^2 = 1/9
2^-2 = 1/2^2 = 1/4

1/9 - 1/4 = -5/36

(-5/36)^-1 = 1/(-5/36) = -36/5

## Similar Questions

1. ### algebra

Which of the following is equivalent to the expression (t2 − t − 6)(t − 3)−1 ?
2. ### calculus

Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
3. ### biology

Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
5. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
6. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …